Toxic in vitro effects of flavoured-air inhalers containing essential oils in differentiated human nasal epithelial cells at air–liquid interface - Alexander N. Larcombe; E. E. Catchpole; P. Hopper; S. Stanley; A. Kicic; K. R. Landwehr (Archives of Toxicology, 2026)
Flavoured-air inhalers containing essential oils are marketed as safe, natural alternatives to smoking and vaping, yet their potential respiratory toxicity remains effectively unexamined. Manufacturers claim safety based on "100% natural" ingredients, despite evidence that essential oil inhalation can cause adverse respiratory effects. Our objective was to assess the in vitro toxicity of six commercially available flavoured-air products on human nasal airway epithelial cells. Differentiated air–liquid interface cultures of primary nasal airway epithelial cells from eight healthy adults were exposed for one hour to air (control) or flavoured air from three devices (Füm, Lio, Cigtrus; two flavours each) generated by drawing air through essential oil-infused cores at a continuous airflow of 1 L/min for one hour into an 1000 mL exposure chamber. Outcomes included transepithelial electrical resistance, cytotoxicity, protein release, cytokine/chemokine profiling and histological assessment. Chemical analysis characterised the chemical composition of device cores and identified 29 compounds across the six products, including the possible carcinogen pulegone and cytotoxic cinnamaldehyde. Five of six flavours significantly reduced transepithelial electrical resistance indicating compromised epithelial barrier integrity. Mediator responses were compartment-specific: apical surfaces showed predominantly pro-inflammatory profiles while basal release was broadly suppressed. Histological analysis revealed reduced cilia coverage, fewer mucus-producing cells, and decreased epithelial thickness across multiple treatments. This study shows that a single one-hour exposure to flavoured-air vapour led to epithelial barrier dysfunction, immune dysregulation, and structural damage in healthy human nasal airway epithelial cells, contradicting manufacturer safety claims. Rigorous toxicological evaluation of these products is urgently needed.

Design for Community Wellness: A Community-Engaged Learning Experience for BME Undergraduate Students - Theo S. Hopper (Biomedical Engineering Education, 2026)
Purpose Community-engaged learning (CEL) has been incorporated into engineering curricula to provide students with authentic design challenges and opportunities to develop professional skills for career-preparedness. This innovation paper describes a novel implementation of CEL in a biomedical engineering (BME) design elective, titled Design for Community Wellness, for undergraduate students. Methods Student teams were partnered with community-based organizations (CBO) to address a community-identified, wellness-focused priority using the human-centered design (HCD) cycle. Surveys with Likert-type questions were used at pre- and post-time points to assess student confidence with engineering skills, course learning objectives, perceived ability to help community with BME, and previously validated metrics of engineering identity, empathy, and engineering self-efficacy. Open response questions were used to further analyze the perceived impact of the course. A survey was also deployed to CBOs to assess the benefits for community members. Results All teams were successful in delivering usable prototypes for their community partners. Student and community partner surveys indicated high satisfaction with the class. No statistical differences were found in any quantitative metrics from pre- and post-surveys, except for a significant increase in confidence hosting user focus groups or interviews. Conclusions In the future, this course will be co-taught with an instructor from the humanities to better prepare students for interactions with community members and to analyze social context for their design projects. Additionally, teams will be multi-disciplinary with engineering and humanities students. Furthermore, alternative strategies will be explored to better assess the impact of this experiment on student development.

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

Embryo and Larval Developmental Staging Guides for Striped Bass - Erimi Kendrick; Nadya Mamoozadeh; William G. Cope; Russell Borski; Robert W. Clark; Michael S. Hopper; Benjamin J. Reading (Fishes, 2026)
Reliable developmental benchmarks are essential for synchronizing incubation and first-feeding decisions in striped bass (Morone saxatilis) hatcheries, yet existing references are incomplete, outdated, or difficult to apply across variable temperature regimes. We developed contemporary embryo and larval developmental staging guides for striped bass using digital imaging and degree day standardization and paired these guides with measurements of early larval mortality and endogenous energy depletion to provide practical context for hatchery management. Larvae were photographed from hatch through metamorphosis to document key morphological transitions, including yolk absorption, mouth formation, swim bladder inflation, fin differentiation, pigmentation, and diet-related developmental milestones. To place these stages in physiological and survival context, aquarium trials showed there was no clear density-dependent mortality across rearing densities of 1.1–6.8 larvae/mL within the first 72 h post-hatch. Yolk reserves were typically depleted by approximately 4–6 days post-hatch (dph), while lipid droplets persisted longer as secondary endogenous energy stores in unfed larvae through 15 dph. Together, these staging guides provide a transferable developmental framework from fertilization to metamorphosis that links external morphology to endogenous reserve depletion and first feeding, thus supporting standardized hatchery monitoring, improved feeding synchronization, and more consistent assessment of embryo and larval quality.

Procedural Variation May Contribute to 6-Minute Walk Distance Variability in Real-World Pediatric Pulmonary Arterial Hypertension Study - Cynthia Kleppinger; Dunbar Ivy; Norman Stockbridge; Angela Bates; Stephanie Handler; Usha S. Krishnan; Mary P. Mullen; Delphine Yung; Rachel K. Hopper; Nidhy P. Varghese; Jeff Fineman; Eric D. Austin; et al. (The AAPS Journal, 2025)
The six-minute walk test (6MWT) is a common method to assess submaximal exercise capacity in children and adults with pulmonary arterial hypertension (PAH) and other chronic diseases. There is no guideline specifically for 6MWT in children. In this observational pilot study, we evaluated the impact of procedural variations on the outcome of the 6MWT in the real-world clinical setting at pediatric PAH programs. We collected 6MWT data from 33 children with PAH participating in a multicenter, prospective, non-interventional study. Data range/quantiles and standard deviation (SD) were used to describe distribution of the six-minute walk distance (6MWD) and data variability. Levene’s test was used to test for heterogeneity of variance with the two sites of similar altitude and their age/height/weight-matched Panama Function Class II participants. We analyzed all 33 eligible participants and their qualified first walks at five centers (A-E) with 6MWD ranges of 420–570, 357–683, 418–481, 400–700, 377–549 m, respectively. Site D performed the 6MWT in a busy hallway and allowed parental/caregiver’s cheering, while Site E performed the 6MWT in a secluded area with no parental/caregiver involvement. Mean 6MWD and SD for Sites D and E were 547 (125) and 432 (67.5) meters, respectively (p = 0.03). In conclusion, procedural variations seem to associate with 6MWD data variability. Although interpretation of our results is limited by the small sample size, our findings suggest that standardizing pediatric 6MWT procedures are needed. Graphical Abstract

Central Artery Hemodynamics in Angiotensin II-Induced Hypertension and Effects of Anesthesia - S. E. Hopper; D. Weiss; N. Mikush; B. Jiang; B. Spronck; C. Cavinato; J. D. Humphrey; C. A. Figueroa (Annals of Biomedical Engineering, 2024)

High content analysis of in vitro alveolar macrophage responses can provide mechanistic insight for inhaled product safety assessment - V. Hutter; S. Hopper; J. Skamarauskas; E. Hoffman (Toxicology in Vitro, 2023)

Applying Research-Based Teaching Strategies in a Biomedical Engineering Programming Course: Introduction to Computer Aided Diagnosis - R. Rosario; T. S. Hopper; A. Huang-Saad (Biomedical Engineering Education, 2022)

Traits related to efficient acquisition and use of phosphorus promote diversification in Proteaceae in phosphorus‐impoverished landscapes - Patrick E. Hayes; Francis J. Nge; Michael D. Cramer; Patrick M. Finnegan; Peili Fu; Stephen D. Hopper; Rafael S. Oliveira; Benjamin L. Turner; Graham Zemunik; Hongtao Zhong; Hans Lambers (Plant and Soil, 2021)

Identification of immucillin analogue natural compounds to inhibit Helicobacter pylori MTAN through high throughput virtual screening and molecular dynamics simulation - Divya S. Raj; Chidhambara Priya Dharshini Kottaisamy; Waheetha Hopper; Umamaheswari Sankaran (In Silico Pharmacology, 2021)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Assessing patient readiness for personalized genomic medicine - Caren J. Frost; Irene L. Andrulis; Saundra S. Buys; John L. Hopper; Esther M. John; Mary Beth Terry; Angela Bradbury; Wendy K. Chung; Katherine Colbath; Natalie Quintana; Elizabeth Gamarra; Brian Egleston; et al. (Journal of Community Genetics, 2019)

Improved quality of risk-reducing salpingo-oophorectomy in Australasian women at high risk of pelvic serous cancer - Y. C. Lee; M. Bressel; P. Grant; P. Russell; C. Smith; S. Picken; S. Camm; B. E. Kiely; R. L. Milne; S. A. McLachlan; M. Hickey; M. L. Friedlander; et al. (Familial Cancer, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

How do researchers manage genetic results in practice? The experience of the multinational Colon Cancer Family Registry - Louise A. Keogh; Douglass Fisher; Sherri Sheinfeld Gorin; Sheri D. Schully; Jan T. Lowery; Dennis J. Ahnen; Judith A. Maskiell; Noralane M. Lindor; John L. Hopper; Terrilea Burnett; Spring Holter; Julie L. Arnold; et al. (Journal of Community Genetics, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Disease-modifying drugs for multiple sclerosis and JC virus expression - Craig S. Miller; Sidney A. Houff; Jason Hopper; Robert J. Danaher; Julie A. Gurwell; Yushun Lin; Nubia Vega; Joseph R. Berger (Journal of NeuroVirology, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Adequacy of risk-reducing gynaecologic surgery in BRCA1 or BRCA2 mutation carriers and other women at high risk of pelvic serous cancer - B. E. Kiely; M. L. Friedlander; R. L. Milne; L. Stanhope; P. Russell; M. A. Jenkins; P. Weideman; S. A. McLachlan; P. Grant; J. L. Hopper; K. A. Phillips (Familial Cancer, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Isoetes eludens (Isoetaceae), a new endemic species from the Kamiesberg, Northern Cape, South Africa - J. P. Roux; S. D. Hopper; R. J. Smith (Kew Bulletin, 2009)

Monocrotophos-Induced Mass Mortality of Swainson's Hawks in Argentina, 1995–96 - Michael I. Goldstein; T. E. Lacher; B. Woodbridge; M. J. Bechard; S. B. Canavelli; M. E. Zaccagnini; G. P. Cobb; E. J. Scollon; R. Tribolet; M. J. Hopper (Ecotoxicology, 1999)

Breast cancer in Australian women under the age of 40 - Margaret R.E. McCredie; Gillian S. Dite; Graham G. Giles; John L. Hopper (Cancer Causes & Control, 1998)